Analisis Pengetahuan Mahasiswa Mengenai Kecerdasan Buatan Berdasarkan Karakteristik Individu - Dhoni Setyanto; Muhammad Taher Jufri; Puji Laksmini (Lembaga Pengembangan Kinerja Dosen, 2025)
Students in higher education are an important target audience for AI education because they need to develop the skills needed to effectively handle AI in their careers. Before we can provide appropriate AI teaching or education to students, data is needed to determine the extent of students' knowledge about AI. The purpose of this study was to determine the level of students' knowledge about AI and what variables could be related to it. The research method used a cross-sectional study design with 132 students and the data were analyzed using the Chi Square test, Mann Whitney, and logistic regression. The results showed that 66.7% of students had high AI knowledge. The results of the bivariate test showed that the independent variable related to the level of AI knowledge in students is the status of AI use. While in the multivariate test, the variables related to the level of AI knowledge are gender and major.